Assessment of the quality of malaria surveillance and laboratory services for diagnosis in three districts of Gujarat state, India - Kaur, Jaspreet; Baharia, Rajendra; Dattani, Mamta (Frontiers in Public Health, 2024)
ObjectivesSurveillance is the backbone for the control of malaria and its elimination. In the state of Gujarat, situated in the western region of India, some of the districts reported a high annual blood examination rate (ABER) for malaria. Therefore, a study was conducted to identify the underlying reasons for the increase in the ABER for malaria.MethodsPlanned investigations were carried out in three of the state districts, scrutinizing records of malaria forms and other epidemiological data collected during health worker surveillance, assessment of laboratory services, and rapid fever surveys.ResultsThe rate of fever ranged from 8 to 57% in the primary health centers that were surveyed. Analysis of epidemiological data revealed that malaria parasite positivity was more from passive than active surveillance. Increased ABER was accounted for by multiple factors, including blood slides collected during the mass survey and contact smears, which were included in the ABER and not mentioned separately. Blood slides prepared for the migrant population were included in the ABER, but the migrant population was not counted while calculating the ABER.ConclusionThe ABER in villages surveyed varied from 1.6 to 78%, which is mainly due to indiscriminate preparation of blood slides, i.e., without fever symptoms. Addressing the key gaps identified in data recording may aid in channeling the limited resources efficiently, thereby progressing toward malaria elimination. Adequate surveillance activities, along with systematic data recording, will enable timely, informed decision-making for the effective allocation of resources, ultimately supporting malaria elimination efforts in the state.